From Homer to Menander Forces in Greek Poetic Fiction. - Post, L. A. (Berkeley : University of California Press, 2022)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1951.
Description based upon print version of record.
JSTOR
Keywords: Homer -- Criticism and interpretation; Greek drama -- History and criticism; Greek fiction -- History and criticism; Greek literature -- History and criticism